Analisis Kualitas Garam Kampung (Tusu’ abuh) Hasil Home Industri Di Desa Ba’Liku, Kecamatan Krayan Tengah, Kabupaten Nunukan, Kalimantan Utara - JosephJoseph (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
This study aims to determine the iodine content of iodine (IO3), the content of iodine content (IO3) and to determine the feasibility of consuming iodine (IO3) village salt (Tusu' abuh) from Home Industry in Ba' Liku Village. The research variable is the analysis of the quality of village salt (Tusu' abuh) from Home Industry in Ba' Liku Village. This research is an analytical descriptive type, with data analysis techniques in the form of explaining the quality of village salt ( Tusu' abuh) from the Home Industry of Ba' Liku Village. The results of the analysis of village salt samples (Tusu' abuh) with the addition of a volume of 5 ml Na2S2O3 then obtained levels of S1 KIO3 as much as 44.94 ppm, adding volume of 5.8 ml Na2S2O3 obtained levels of S2 KIO3 as much as 44.14 ppm, and adding volume 16.1 ml Na2S2O3 obtained levels of S3 KIO3 as much as 33.85 ppm. The total average of the results of weighing village salt samples (Tusu' abuh) was 40.97 ppm. Village salt (Tusu' abuh) is categorized as having adequate levels of iodine in accordance with the regulations of the Indonesian National Standard (SNI Number 01-3556-2010) which contains iodine of 30-80 ppm. From the analysis of consumption feasibility research, village salt (Tusu' abuh) still contains impurities that can harm the body, so this salt is categorized as unsafe (not yet feasible) to be used as household consumption.